Judicial Independence and Rule of Law: A Comparative Legal Policy Review - Sahal Hanafi; Ekberth Valen Noya (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
This study examines judicial independence and the rule of law through a non-empirical, doctrinal-comparative legal policy approach that integrates constitutional interpretation, statutory analysis, and cross-jurisdictional jurisprudence. Drawing upon primary legal instruments, including constitutional provisions, statutes, governmental regulations, and landmark judicial decisions, alongside comparative scholarship, the research analyzes how formal guarantees of independence are operationalized through institutional mechanisms and enforcement practices. The findings demonstrate that judicial independence is multidimensional, encompassing structural safeguards, procedural integrity, disciplinary autonomy, and collective professional agency. Comparative assessment between Indonesia and European Union member states reveals that multilayered enforcement, including supranational judicial oversight, strengthens resilience against executive encroachment, populist intervention, and emergency governance expansion. The study further identifies the interdependence between independence and legal certainty, public trust, and economic stability, arguing that independence acquires substantive meaning only when embedded in enforceable and context-sensitive institutional frameworks. The research contributes theoretically by refining the conceptual integration of autonomy and accountability, and methodologically by advancing structured doctrinal-comparative analysis within contemporary constitutional scholarship.